2018
DOI: 10.1111/joca.12218
|View full text |Cite
|
Sign up to set email alerts
|

App Users Unwittingly in the Spotlight: A Model of Privacy Protection in Mobile Apps

Abstract: Mobile apps are increasingly jeopardizing app users' online privacy by collecting, storing, and sharing personal data disclosed via apps. However, little is known about mobile app users' current privacy protection behavior and the factors that motivate it. Drawing on Roger's Protection Motivation Theory (PMT), this study develops and tests the App Privacy Protection Model among 1,593 Western European app users. The results demonstrate that, on the one hand, increased levels of perceived self‐efficacy, vulnerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 47 publications
(118 reference statements)
4
35
1
1
Order By: Relevance
“…We made sure to account for the generally low knowledge level (Smit et al, 2014) by not simply measuring, but by manipulating it. Also, we hoped to maximize the effect by narrowing down the manipulation to a specific context, i.e., Google (as past studies have concluded that insignificant effects could be explained by too general measures, e.g., Wottrich et al, 2018). However, the effect was small and opposite to our expectation.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…We made sure to account for the generally low knowledge level (Smit et al, 2014) by not simply measuring, but by manipulating it. Also, we hoped to maximize the effect by narrowing down the manipulation to a specific context, i.e., Google (as past studies have concluded that insignificant effects could be explained by too general measures, e.g., Wottrich et al, 2018). However, the effect was small and opposite to our expectation.…”
Section: Discussionmentioning
confidence: 82%
“…First, technical knowledge has been identified as one of the main predictors of health information privacy concern (Ermakova Fabian, Kelkel, Wolff, & Zarnekow, 2015). Second, more concerned individuals have been found to refrain from using certain apps (Wottrich, Van Reijmersdal, & Smit, 2018), or reject cookies that enable personalization (Milne & Culnan, 2004). Thus, we argue that privacy concern needs to be added as a factor within the threat appraisal that is impacted by technical knowledge and motivates users to opt-out from personalization.…”
Section: Explaining Empowering Impact Of Knowledge Through Pmtmentioning
confidence: 92%
See 3 more Smart Citations